2010
DOI: 10.5851/kosfa.2010.30.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Medium Optimization for the Production of Probiotic Lactobacillus acidophilus A12 Using Response Surface Methodology

Abstract: Lactobacillus acidophilus A12 was isolated from chicken feces for use as an immunostimulating livestock probiotic. The purpose of this study was to optimize the production of L. acidophilus A12 using response surface methodology (RSM). Initially, the influence of growth medium was studied in terms of carbon sources (glucose, fructose, lactose, glycerol, sucrose, ethanol, and mannitol), nitrogen sources (beef extract, yeast extract, malt extract, and tryptone), and inorganic salts (CaCl , and NaCl). Through one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, 0.15% magnesium sulfate was foremost important salt that could stimulate GSH production and cell growth. Lee et al (2010) reported similar effect for magnesium sulfate on L. acidophilus A12. In the present work, all the above media components were already included in MRS in addition to other ingredients that are sufficient to enhance the cell density and GSH productivity.…”
Section: Resultsmentioning
confidence: 61%
“…Furthermore, 0.15% magnesium sulfate was foremost important salt that could stimulate GSH production and cell growth. Lee et al (2010) reported similar effect for magnesium sulfate on L. acidophilus A12. In the present work, all the above media components were already included in MRS in addition to other ingredients that are sufficient to enhance the cell density and GSH productivity.…”
Section: Resultsmentioning
confidence: 61%
“…After optimization, the optimum medium components for biomass production were found to be 17.7 g/L lactose, 18.6 g/L yeast extract, and 0.9 g/L CaCl2. Under these conditions, a maximum cell density of 9.33 Log CFU/mL was produced (Lee et al, 2010) . The growth kinetics of probiotic Lactobacillus strains in the alternative, costefficient semi-solid fermentation medium was studied by Śliżewska and Chlebicz-Wójcik (2020).…”
Section: Resultsmentioning
confidence: 99%